Assessing the reliability of ChatGPT in cytogenetic reporting and interpretation: implications for clinical use - Alain Chebly; Lauren Veronese; Edith Chevret (Molecular Cytogenetics)
Abstract This study evaluates the accuracy of ChatGPT in generating chromosomal representations (formulas) based on ISCN rules in clinical cytogenetics. While ChatGPT generated correct answers for simple cases, it frequently failed in complex cases. These findings highlight the limitations of current AI tools in accurate clinical cytogenetic reporting, reinforcing the vital role of skilled clinical cytogeneticists for accurate interpretation and reporting.